Initiation of self-care practices in heart failure patients: a phenomenological study - Suharsono, Tony; Ulya, Ikhda; Yona , Sri; Siswanto , Bambang Budi (Universitas Airlangga, 2024)
Introduction: The incidence of heart failure continues to rise with advancing age, unabated by advancements in healthcare technology. Patients with heart failure are required to manage their care independently at home for the remainder of their lives. This study aimed to delve into the experiences of heart failure patients regarding self-care management at home. Methods: Nineteen patients with heart failure were chosen through purposive sampling and thorough interviews were conducted to collect their self-care treatment experiences. Content analysis was carried out to scrutinize the acquired data. Results: The analysis revealed four themes: patients' perception of heart failure diagnosis, efforts in self-care, readiness for self-care, and adoption of new healthy behaviors in heart failure. Eight categories were formulated within these themes, including